A 12-point recommendation framework to support advancement of the multidisciplinary care of psoriatic arthritis: a call to action - Gratacós, J; Behrens, F; Coates, LC; Lubrano, E; Thaçi, D; Bundy, C; de la Torre-Aboki, J; Luelmo, J; Voorneveld, H (Elsevier, 2021)
Objective: Making a differential diagnosis of psoriatic arthritis (PsA) is not straightforward. This is partly because of its heterogeneous presentation and partly because many patients with PsA are initially diagnosed with psoriasis and treated in primary care or by dermatologists, with referral to rheumatologists being delayed. Once diagnosed, optimal disease control requires frequent specialist monitoring, adjustment or switching of therapies, and management of comorbidities and concomitant diseases, as well as attention to patients’ overall well-being. Given the breadth of expertise that diagnosis and management of PsA requires, we sought to define a collaborative, structured framework that supports the optimisation of multidisciplinary care for patients with PsA in Europe.